Pengembangan Hydrosphere Mobile Learning (HML) untuk Meningkatkan Minat dan Hasil Belajar Geografi - Indrawati, Welly; Amin, Saiful (Universitas Prof. Dr. Hazairin, S.H, 2023)
The use of monotonous learning media causes students to tend to feel bored and pay less attention to the teacher when explaining the material. This condition leads to lack of interest on learning in students towards geography. In addition, it also has an impact on learning outcomes that are less than optimal. The aims of this research were (1) to determine the feasibility of HML on hydrosphere material, (2) to find out the effect of HML on the learning interest, and (3) to figure out the influence of HML on the geography learning outcomes. Lee & Owen’s Research and Development (R&D) model was conducted on this research. 30 X IPS 1 students as the experimental group and 30 X IPS 2 students as the control group in MA Al Hidayah Wajak, Kabupaten Malang were participated in this research. Observation, interviews, questionnaires, pre-test, and post-test, as well as documentation were used to collect the data. The qualitative data was analyzed by analyzing the suggestions and criticisms given by the material expert, the media expert, and students, whilst questionnaire analysis by the material expert, the media expert, students, and mean analysis were conducted to analyzed the quantitative data in this research. Furthermore, independent sample t-test was also tested to examine the effect of the used of HML. The results showed that (1) based on the evaluation by the material expert and the media expert, an average score of 96% was obtained, which meant HML was suitable for geography’s hydrosphere material learning, (2) the used of HML had a positive effect on the learning interest with sig. 0,000 < 0,05, and (3) HML media had a positive effect on the geography learning outcomes with sig. 0,000 < 0,05.